Political discourse of history and action in the political project of José De Alencar during imperial Brazil - Lyra Alves, Marcus A. (Culture and religion, 2020)
José de Alencar (1829–1877) is one of the most relevant names in Brazilian Romantic literature of the nineteenth century, and an important politician of the Conservative Party. This work attempts to provide a glimpse of major influences from European Romanticism, highlighting the way it brought a Christian notion of a linear and positivist history to Brazilian political arena. A documental research is made on two non-literary publications: Systema Representativo (1868) and A Propriedade (posthumously published in 1883) seeking to pinpoint the notion of iconic linear time as an ideological colonisation of political discourses through the Romantic stylistic approach of Alencar.